Kontribusi Beban Kerja terhadap Burnout pada Karyawan CV. Jaya Subur Abadi di Kota Payakumbuh - Putri, Dini Aulia; Guspa, Anandra (Al-DYAS, 2024)
Of course, good performance will not be created if employees experience emotional exhaustion or low self-esteem, or what is usually called burnout. This research aims to see the contribution of workload to CV employee burnout. Jaya Subur Abadi. This research is a quantitative research. The population in this study were employees of CV. Jaya Subur Abadi. Research was conducted on all employees who work at CV. Jaya Subur Abadi. Data collection was carried out using a workload and burnout scale. The analysis used in the research is simple linear regression analysis. Based on the results of data processing that has been carried out, the contribution value of workload to burnout is 37.2%.